Dual Antibiotic Prophylaxis in Primary Total Knee Arthroplasty—No Benefit for Extremely Obese Patients - Lane, Mark K.; Keeney, James A. (The Journal of Knee Surgery, 2021)
We performed this study to assess the effectiveness of multimodal total knee arthroplasty prosthetic joint infection (TKA-PJI) prophylaxis including “on-time” dual-antibiotic prophylaxis, and the influence of body mass index (BMI) on prophylaxis effectiveness. After obtaining Institutional Review Board approval, we assessed 1,802 primary TKAs (1,496 patients) who received cefazolin alone or cefazolin combined with vancomycin for TKA-PJI prophylaxis. A detailed chart review was performed to determine patient demographic features (age, gender, BMI, American Society of Anesthesiologists Score), antibiotic selection, vancomycin administration timing, and 1-year PJI rates. Statistical assessment was accomplished using a two-sided Student's t-test or Fisher's exact test. Patients who received dual-antibiotic prophylaxis with “on time” vancomycin infusion (Group CVt) had significantly lower infection rates than other TKA patients (0.8 vs. 2.7%, p < 0.01). “On Time” vancomycin administration was associated with a lower TKA-PJI rate for patients with a BMI < 45 kg/m2 (0.5 vs. 2.6%, p < 0.01) with no infections in 120 TKA patients with a BMI between 40 and 44.9 kg/m2 (p < 0.01). No difference was noted for patients with a BMI ≥ 45 kg/m2 (3.3 vs. 2.6%, p = 0.71). There were no infections in 150 TKA patients with a normal BMI (18–25 kg/m2) in any PJI-prophylaxis treatment group. Adoption of a dual-antibiotic prophylaxis approach can successfully reduce TKA-PJI rates among overweight and moderately obese patients. The approach does not appear to influence outcomes for low risk patients with a normal BMI (18–25 kg/m2) or for higher risk patients with a BMI > 45 kg/m2.
Keywords: prosthetic joint infection; vancomycin; dual-antibiotic; total knee arthroplasty; total hip arthroplasty; total joint arthroplasty